2000
DOI: 10.2337/diabetes.49.9.1399
|View full text |Cite
|
Sign up to set email alerts
|

The need for early predictors of diabetic nephropathy risk: is albumin excretion rate sufficient?

Abstract: Initial studies showing an ~80% rate of progression from microalbuminuria (MA) to proteinuria in type 1 diabetic patients led to the broad acceptance of MA as a useful clinical predictor of increased diabetic nephropathy (DN) risk. Some MA patients, however, have quite advanced renal structural changes, and MA may, in these cases, be a marker rather than a predictor of DN. More recent studies have observed only about a 30-45% risk of progression of MA to proteinuria over 10 years, while about 30% of type 1 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
266
1
12

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(287 citation statements)
references
References 81 publications
8
266
1
12
Order By: Relevance
“…These findings are supported by the fact that zinc in serum may not affected by increasing blood pressure. It has been reported that as hypertension is a potent risk factor for microalbuminuria [17], it seems that the increase albumin excretion is dependent of change in blood pressure. However, the present study showed that the mean serum zinc level was not significantly differing between diabetic normotensive (group II) and hypertensive patients (group III).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by the fact that zinc in serum may not affected by increasing blood pressure. It has been reported that as hypertension is a potent risk factor for microalbuminuria [17], it seems that the increase albumin excretion is dependent of change in blood pressure. However, the present study showed that the mean serum zinc level was not significantly differing between diabetic normotensive (group II) and hypertensive patients (group III).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, detection of microalbuminuria in the higher range identifies those patients with a particularly high risk of clinical nephropathy. In fact, the rate of progression from microalbuminuria to clinical albuminuria and the significance of microalbuminuria as a predictor of diabetic nephropathy have been a matter of debate [12,13]. Early retrospective studies described a risk of progression from microalbuminuria to macroalbuminuria of approximately 80% in 6 to 14 years (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic nephropathy is expected to remain the leading cause of end stage renal failure in the Western world, despite the recent therapeutic advances brought about by the angiotensin receptor blockers. Albuminuria is an early and easily measurable biomarker of nephropathy [14]. The extent of albuminuria correlates with the risk of future cardiovascular events (myocardial infarction, stroke) and predicts the incidence of end stage renal failure even before retention parameters such as creatinine are increased in the serum [2,15].…”
Section: Discussionmentioning
confidence: 99%